Ultrasound molecular imaging of E-selectin in tumor vessels using poly n-butyl cyanoacrylate microbubbles covalently coupled to a short targeting peptide - Fokong, Stanley; Fragoso, Ana; Rix, Anne; Curaj, Adelina; Wu, Zhuojun; Lederle, Wiltrud; Iranzo, Olga; Gätjens, Jessica; Kiessling, Fabian; Palmowski, Moritz (Investigative radiology, 2013)
The purposes of this study were the development and preclinical evaluation of clinically translatable E-selectin-specific ultrasound contrast agents based on a peptide ligand with the recognition sequence IELLQAR. - The E-selectin-specific peptide was synthesized through solid phase peptide synthesis and covalently attached to poly n-butylcyanoacrylate-stabilized microbubbles with an air core. Quantification of the microbubble surface coverage with peptides was performed through flow cytometry. Targeted adhesion of peptide-coated microbubbles was investigated in vitro using parallel plate flow chamber assays on tumor necrosis factor-α-stimulated human umbilical vein endothelial cells. In vivo imaging was performed in nude mice bearing human ovarian carcinoma xenografts (MLS), followed by ex vivo immunohistochemistry validation of E-selectin expression. - Success of peptide synthesis was validated through preparative reverse phase high-pressure liquid chromatography and electronspray ionization-mass spectrometry. Results of the flow cytometry revealed approximately 4000 E-selectin-specific peptides/microbubble surface. Results of the in vitro experiments demonstrated the specificity of peptide-coated microbubbles to E-selectin (1.10 ± 0.48 vs 0.19 ± 0.09 bound microbubbles per cell, before and after competition respectively; P < 0.01). The in vivo imaging enabled specific assessment of E-selectin expression in MLS carcinoma xenografts (5.21 ± 3.41 vs 1.37 ± 0.67 contrast intensity before and after competition, respectively; P < 0.05). - Clinically translatable microbubbles that were covalently coupled to the short E-selectin-specific peptide (IELLQAR) enabled specific imaging of the E-selectin expression in tumor vessels in vivo.